2018
DOI: 10.1096/fj.201800852rr
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of chondroitin‐4‐sulfotransferase‐1, but not of dermatan‐4‐sulfotransferase‐1, accelerates regeneration of zebrafish after spinal cord injury

Abstract: Glycosaminoglycans such as chondroitin sulfate (CS) and dermatan sulfate (DS) are long chains of repeating disaccharide units, covalently linked to core proteins to form proteoglycans. Proteoglycans can be cell membrane‐bound or are part of the extracellular matrix. They are important in a wide range of biologic processes, including development, synaptic plasticity, and regeneration after injury, as well as modulation of growth factor signaling, cell migration, survival, and proliferation. Synthesis of CS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Of interest, zebrafish express sulfotransferases that may influence the sensitivity of PNN components to proteolysis (Habicher et al., 2015; Sahu, Li, Loers, & Schachner, 2019). Knockdown of chondroitin‐4‐sulfotransferase in zebrafish, which generates neuroplasticity‐restricting 4‐sulfated chondroitin sulfate‐glycosaminoglycans in rodents (Foscarin, Raha‐Chowdhury, Fawcett, & Kwok, 2017), accelerates regeneration following spinal cord injury (Sahu et al., 2019). This result is consistent with conserved mechanisms by which ECM affects neuroplasticity in diverse organisms.…”
Section: Antidepressants and Pnn Modulationmentioning
confidence: 99%
“…Of interest, zebrafish express sulfotransferases that may influence the sensitivity of PNN components to proteolysis (Habicher et al., 2015; Sahu, Li, Loers, & Schachner, 2019). Knockdown of chondroitin‐4‐sulfotransferase in zebrafish, which generates neuroplasticity‐restricting 4‐sulfated chondroitin sulfate‐glycosaminoglycans in rodents (Foscarin, Raha‐Chowdhury, Fawcett, & Kwok, 2017), accelerates regeneration following spinal cord injury (Sahu et al., 2019). This result is consistent with conserved mechanisms by which ECM affects neuroplasticity in diverse organisms.…”
Section: Antidepressants and Pnn Modulationmentioning
confidence: 99%
“…ECM remodeling is thought to be crucial for functional recovery from SCI; for instance, in mice, ECM proteins such as CSPGs are upregulated after injury and can inhibit the growth of axons (Dyck and Karimi-Abdolrezaee, 2015). In zebrafish, morpholino knockdown of Chondroitin-4-sulfotransferase-1, a sulfotransferase important in the synthesis of CSPGs, enhanced the speed of spinal cord regeneration in both larvae and adults, suggesting that this mechanism is conserved between zebrafish and mouse (Sahu et al, 2019). After SCI in zebrafish, the expression of ostensibly growthpermissive ECM components (like Ctgfa) is induced in both neural and non-neural tissues within the injured spinal cord.…”
Section: Environmental Propertiesmentioning
confidence: 99%
“…Furthermore, extracellular matrix from mouse limbs is capable of inducing limb pattern in axolotl blastemas in a position‐specific, developmental‐stage‐specific, and heparan sulfate‐dependent manner. Furthermore, Sahu et al demonstrated that knockdown of chondroitin‐4‐sulfotransferase‐1, but not of dermatan‐4‐sulfotransferase‐1, accelerates regeneration of zebrafish after spinal cord injury, indicating that chondroitin sulfate and dermatan sulfate structures play different roles in axonal regeneration (Sahu, Li, Loers, & Schachner, ). When using immunohistochemistry to examine the expression of two chondroitin sulfates with different sulfation variants at the lesion site in the spinal cord of goldfish, Takeda et al showed that chondroitin sulfate is co‐localized with the regenerating axons (Takeda, Okada, & Funakoshi, ).…”
Section: Axolotls As Spinal Cord Regeneration Modelsmentioning
confidence: 99%